Multilateral Economic Ties of Mongolia with its Asian Trading Partners in period of 2011-2021 (Mongolian Journal of International Affairs, 2022)
This article gives insight of main aspects of Mongolian’s economy related to its Asian Trading Partners namely China, India, South Korea and Japan in period of 2011-2021. To give more clarity about the main trading partners of Mongolia there are two countries: China and Russia, but the author focuses only on the Asian trading partners. The main goal is to popularise still not well known economy of Mongolia and to see how it was developed in analysed period of 2011-2022. As the methodology of the research the author used empirical analysis based mainly on Macrobond data which also has access to Mongolian Statistics Office data and also to available world reports such OECD, UNCTAD. Besides that, the article was consulted with Mongolian Ambassador in Poland and it was enriched this way with his best knowledge regarding economy and Mongolia international trade and investment policy. The interesting aspect which was raised by the author in this article was the future state of economy of Mongolia after pandemic of SARSCoV-2 and impact of the restrictions imposed on Russia due to the war on Ukraine